Primary mediastinal clear cell sarcoma: a case report and review of the literature - Jin, Long (Diagn Pathol, 2017)
BACKGROUND: Clear cell sarcoma (CCS) is a rare malignant soft-tissue neoplasm that displays melanocytic markers and exhibits striking histopathological features. The tumour has a predilection for the lower extremities and rarely presents in the mediastinum. CASE PRESENTATION: We present a case of primary mediastinal CCS in a 57-year-old man. Computer tomography (CT) revealed a 12 × 12 × 7.5 cm mass in the anterior mediastinum. Microscopically, the tumour mainly consisted of epithelioid cells with oval vesicular nuclei and eosinophilic cytoplasm. Immunohistochemically, the tumour was positive for human melanoma black 45 (HMB-45) and vimentin but negative for S-100 and Melan-A. Fluorescence in situ hybridisation (FISH) showed a translocation involving the EWSR1 gene region. CONCLUSION: This report will illustrate that the mediastinum is a potential site for primary CCS and FISH plays an important role in making a conclusive diagnosis.